Arthroscopic Distal Clavicle Bone Bock Combined With Hill-Sachs Remplissage for Primary Anterior Shoulder Instability Treatment - Nicolas Bonnevialle, M.D., Ph.D.; Antoine Baltassat, M.D.; Vincent Martinel, M.D.; Hugo Barret, M.D.; Pierre Mansat, M.D., Ph.D. (Arthroscopy Techniques, 2024)
Arthroscopic distal clavicle transfer is an effective option to treat anterior shoulder instability with glenoid bone loss. The use of this free bone graft in an all-inside procedure, with a cortical button fixation makes the construct simpler to perform and allows to be combined with a Hill-Sachs Remplissage to address humeral bone defect. The morbidity of the donor site is low and provide the biologic capacity of an autograft. We report a step-by-step procedure, and the rationale are discussed.